Aturan Yang Digunakan Masyarakat Adat Untuk Pelestarian Lingkungan - Sri Handayani; Alimas Jonsa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Indigenous peoples often live and survive in a natural environment that holds a variety of exotic wealth, both in terms of natural and human resources and customs as their culture. Indigenous peoples are often at the forefront of defending natural resources because that is where they live. However, indigenous peoples are also affected by external damage such as pollution and their natural conditions are resistant to natural disasters. The purpose of this research is to analyze the rules in use of the Tengger indigenous people in Pandansari Village, Poncokusumo Subdistrict, Malang Regency to preserve their environment. Rules in use is a parameter found in Institutional Analysis and Development (IAD) which is commonly used to analyze neo-institutionalism public policies, especially Rational Choice Institutionalism (RCI). This research was conducted in mid-2023. This research uses qualitative methods with data collection techniques through interviews and documentation. Furthermore, the results of the interview were analyzed with a coding process using N-Vivo 12 Plus. The results of this study indicate that the Tengger indigenous people in Pandansari village, Poncokusumo sub-district, Malang Regency implement rules that naturally arise from the ideas and ideas of the community itself by gathering in a disaster response community. Where the community is engaged in self-help groups based on collective awareness, namely concern, then the government at the regional and village levels provides a legal umbrella for the community.